1989
DOI: 10.1128/jcm.27.1.29-34.1989
|View full text |Cite
|
Sign up to set email alerts
|

Dot hybridization assay for distinction of rotavirus serotypes

Abstract: We have developed a hybridization assay that permits distinction of rotavirus serotypes 1, 2, 3, and 4. The serotype of rotaviruses from stool samples or tissue culture was recognized by hybridization of specific probes to (i) blots of viral double-stranded RNAs electrophoresed in agarose gels (Northern blots) or (ii) heatdenatured double-stranded RNAs directly dotted on nylon membranes. The probes consisted of 32P-labeled cDNA synthesized by reverse transcription of in vitro derived rotavirus mRNA from rotavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…These ss transcripts served as the template for producing radiolabelled probes to the VP7 (serotype-specific) and the VP4 (type-specific for the virulence phenotypes of the virus) genes. Avian myeloblastosis virus (AMV) reverse transcriptase was used to produce the copy DNA probes with synthetic oligonucleotide primers directed at nucleotides 375 to 391 of the VP7 gene mRNA (5' GATCCTGTTGGCCATCC 3') and nucleotides 551 to 530 of the VP4 mRNA (5' GGTGTTTCAC-CATGAAACGTCC 3') as developed by Flores et al [1989] and kindly donated to this laboratory. Approximately 100 ng of the VP4 or VP7 primers were mixed with 1-4 pg of total ssRNA.…”
Section: Preparation Of Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…These ss transcripts served as the template for producing radiolabelled probes to the VP7 (serotype-specific) and the VP4 (type-specific for the virulence phenotypes of the virus) genes. Avian myeloblastosis virus (AMV) reverse transcriptase was used to produce the copy DNA probes with synthetic oligonucleotide primers directed at nucleotides 375 to 391 of the VP7 gene mRNA (5' GATCCTGTTGGCCATCC 3') and nucleotides 551 to 530 of the VP4 mRNA (5' GGTGTTTCAC-CATGAAACGTCC 3') as developed by Flores et al [1989] and kindly donated to this laboratory. Approximately 100 ng of the VP4 or VP7 primers were mixed with 1-4 pg of total ssRNA.…”
Section: Preparation Of Probesmentioning
confidence: 99%
“…Several identical membranes were prepared from each set of RNAs and each membrane contained controls of known VP7 and VP4 specificity. Hybridisation was performed as described by Flores et al [1989]. Briefly, the membranes were pre-hybridised for 1-2 h r a t 51°C in a mixture containing 50% formamide, 4 x SSC, 40 mM sodium buffer (pH 6,5), 0,2%) SDS, and 2 x Denhardt's solution.…”
Section: Hybridisation Analysismentioning
confidence: 99%
“…Dot blot hybridization assays have been utilized by a number of groups both for the detection of human rotavirus in clinical samples (Flores et al, 1983;Pedley and Mc-Crae, 1984) and for the detection and characterization of enteric coronavirus infection of baby pigs (Shockley et al, 1987 ). Additional studies have been reported in which improved cDNA probes of gene-specific segments of the rotavirus genome were used to characterize human rotavirus by subgroup and serotype (Dimitrov et al, 1985;Lin et al, 1987;Flores et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Practical application of the dot blot hybridization assay may require some modification. These include densitometry to minimize subjective comparisons of the reactions, the use of probes representing gene 4 that encodes VP4, and the construction of cDNA probes from selected regions in which highly conserved bases at the 5' end have been removed (Flores et al, 1989). Specific regions of DNA can now be amplified using synthetic oligonucleotides by polymerase chain reaction (PCR) and used as probes.…”
Section: Discussionmentioning
confidence: 99%
“…In another study spot hybridization was found to be more sensitive than culture for detection of CMV in buffy coats (Spector et al, 1984). When applied to viruses not routinely isolated, such as rotavirus (Flores et al, 1983), enteric adenoviruses (Stalhandske et al, 1983(Stalhandske et al, , 1985Takiff et al, 1985), parvoviruses (Clewley, 1985;Anderson et al, 1985); papovaviruses (Gibson et al, 1985;Wickenden et al, 1985) and Epstein-Barr virus (Andiman et al, 1983), spot hybridization could prove useful. Detection of HBV-DNA in serum by spot hybridization correlates with active virus replication (Carloni et al, 1987).…”
Section: Viral Genome Detectionmentioning
confidence: 99%